2014
DOI: 10.9790/3021-04841832
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Variable Fluid Viscosity of Non-Darcian Flow over a Moving Vertical Plate in a Porous Medium with Suction and Viscous Dissipation

Abstract: -An analysis is carried out to study free convective flow and heat transfer of a viscous incompressible fluid over a linearly moving vertical porous plate with suction and viscous dissipation. The fluid viscosity is assumed to vary as a linear function of temperature. The governing boundary layer equations are reduced to boundary value problem using the concept of similarity transformations. The corresponding coupled ordinary differential equation is solved numerically using the Runge Kutta fourth order method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Technically, the magnitude of the Lorentz forces is easily adjustable over time by exerting a periodic electric current of higher frequency. This control manner is more practical than other known techniques, like the porosity of rigid surfaces and their roughness impact as explained by Mutschke et al 1 In a numerical analysis by Animasaun and Aluko, 2 it was demonstrated that the magnetic field retards the motion of the fluid and the suction effect stabilizes the establishments of the hydrodynamic and thermal boundary layers. Besides this, Zaydan et al 3 found that the increase in the blowing process tends to boost the temperature distribution across the fluidic medium and lead to higher thermo-magneto-hydrodynamic stability as compared with the suction case.…”
Section: Introductionmentioning
confidence: 94%
“…Technically, the magnitude of the Lorentz forces is easily adjustable over time by exerting a periodic electric current of higher frequency. This control manner is more practical than other known techniques, like the porosity of rigid surfaces and their roughness impact as explained by Mutschke et al 1 In a numerical analysis by Animasaun and Aluko, 2 it was demonstrated that the magnetic field retards the motion of the fluid and the suction effect stabilizes the establishments of the hydrodynamic and thermal boundary layers. Besides this, Zaydan et al 3 found that the increase in the blowing process tends to boost the temperature distribution across the fluidic medium and lead to higher thermo-magneto-hydrodynamic stability as compared with the suction case.…”
Section: Introductionmentioning
confidence: 94%
“…The viscous dissipation effects in the entrance region heat transfer in pipes with uniform heat flux were analyzed by Ou and Cheng [13]. This attracted Animasaun and Aluko [14] to study free convective flow and heat transfer of a viscous incompressible fluid over a linearly moving vertical porous plate with suction and viscous dissipation; hence, reported that temperature function is an increasing function of Eckert number. Radiation and viscous dissipation effects on unsteady free convective flow past a moving vertical plate in a porous medium were considered by Das et al [15].…”
Section: Introductionmentioning
confidence: 99%
“…Anjali and Prakash [31] investigated the thermal conductivity impacts on steady incompressible magnetohydrodynamic fluid flow over a non-uniform stretching surface.Makindeet al [32] investigated the combined impacts of convective heating, Buoyancy force, magnetic field, thermophoresis and Brownian motion on stagnation point flow and heat transfer due to nanofluid stream over a stretching surface.The impact of temperature-dependentviscosity on free convective stream over a permeable plate was examined by Makinde and Ogulu [33] with thermal radiation,magnetic field and a first-order homogeneous chemical reaction. Sreedeviet al [34] focused cross diffusion and joule heating impacts of magnetohydrodynamic flow past a porous vertically stretching sheet in the presence of viscous dissipation, Buoyancy force and thermal radiation.Some researcher's [35][36][37][38][39] have discussed and reported the effects of non-linear thermal radiation over a vertical plate.…”
mentioning
confidence: 99%